A socio-eco-efficiency analysis of integrated and non-integrated crop-livestock-forestry systems in the Brazilian Cerrado based on LCA - Costa, Marcela P. [UNESP]; Schoeneboom, Jan C.; Oliveira, Sueli A.; Viñas, Rafael S.; de Medeiros, Gerson A. [UNESP] (Elsevier, 2018)
Crop-livestock-forest (CLFi) and crop-livestock (CLi) systems are among the most recent agricultural developments in Brazil, and aligned with the principles of cleaner production. Such integrated systems can provide at least three types of product from the same land area over a defined period. This paper presents a holistic sustainability evaluation using life cycle assessment to compare combinations of integrated and conventional systems in the Brazilian Cerrado region. The study assesses a comprehensive set of indicators in the three sustainability dimensions: environmental, economic, and social (socio-eco-efficiency). By prioritizing CLFi, the production area to meet the demand of grains, meat and energy for 500 Brazilians, from 2007 to 2014, reached 70 ha, while the conventional systems would need 420 ha to meet the same demand. This result shows that it is possible to increase production to meet the growing food global demand without the need of expanding the agricultural frontier, preserving the remaining forestland. CLFi combinations systems decreased 55% in climate change potential (2389 t of CO2 equivalent), when compared to the conventional systems. It was also observed that the more integrated systems improved the quality of employment, promoted future generation investments in society, and decreased the total production costs in 54%, when compared to conventional systems. Therefore, intensification achieved through good practices such as association, rotation, and succession by an agroforestry system, optimization of inputs (including water, energy, fertilizers, and crop protection agents), land use, soil quality, biodiversity and social aspects.
Keywords: Climate change potential; Economic assessment; Environmental fingerprints; Social impact assessment; Sustainable development